Hubungan antara Keadilan Distributif dengan Organization Citizenship Behavior pada Karyawan - Devana, Nathasya; Mulyana, Olievia Prabandini (Jurnal Global Ilmiah, 2025)
In a dynamic organizational environment, employee behavior and attitudes are essential for superior performance, with workplace justice being a crucial aspect. Distributive justice, as a main pillar of organizational justice, focuses on employees' perceptions of the fairness of outcomes such as compensation, promotions, and workload, influencing prosocial behaviors like Organizational Citizenship Behavior (OCB). This study aims to examine the relationship between distributive justice and OCB among permanent production operator employees at PT.X. Employing a quantitative approach with a correlational explanatory survey design, data were collected from 100 respondents using Likert scale questionnaires. The data analysis results show a Pearson correlation coefficient of 0.836 with a significance value of 0.000 (p < 0.01), indicating a strong and significant positive relationship between distributive justice and OCB. These findings are consistent with Social Exchange Theory and Equity Theory, affirming that perceptions of distributive justice encourage voluntary employee behaviors beyond formal job requirements. This research offers theoretical contributions to the antecedents of OCB and provides practical implications for human resource management in Indonesia to foster a fair work environment that encourages OCB.